Sustainability Checklist for Transport System Plan for Mangrove Eco-Park - Moch Zamani Achmad; Syed Ahmad Iskandar Syeed Arifin; Ahmad Faizal Ahmad Fuad; Asmawi Abdul Malik; Ismail Zainol (International Journal of Marine Engineering Innovation and Research, 2018)
Preservation of mangrove, like efforts on preservation of other natural ecosystem, is directly connected to sustainability. Eco-park as one model of mangrove eco-tourism is well accepted worldwide. Mangrove eco-park comprises of accommodations, edutainment centre, galleries, restaurants, etc. If these facilities are not properly planned and sustainability elements are not incorporated they will have negative effects to the preservation effort. The incorporation of sustainability elements in planning is already a standard practice by many district councils in developed countries like US and UK. Developers are to conform to the sustainability checklists failing which their project many not be approved. To be able to accommodate all type of development proposal the checklists are generic. Conformation to sustainability is required overall rather than the project systems and sub-systems. Therefore the checklists can be used for control purposes but with great limitations. System specific sustainability is required. This study identifies the generic model of a typical mangrove eco-park systems, sub and sub-sub systems and proposed their individual primary sustainability elements. A simplified model has been applied to the planning of transport system for Tanjong Pelepas Eco-Park (TPEP), a mangrove preservation effort by a Malaysian Port Authority. Thirty three eco-park sub-sub-systems have been prioritised and their primary sustainability elements identified. Parties responsible for the sustainability elements, either designer or TPEP operator, or both have been identified. The checklist is expandable and could be used to develop TPEP’s standard operating procedures.